Aerodynamic Characteristics Over Fine-Grained Gravel Surfaces in a Wind Tunnel - Liu, Jiaqi; Kimura, Reiji; Wu, Jing (Frontiers in Earth Science, 2021)
Gravels can protect soil from wind erosion, however, there is little known about the effects of fine-grained gravel on aerodynamic characteristics of the near-surface airflow. Drag coefficient, wind-speed gradient, and turbulent transfer coefficient over different coverages of gravel surfaces were investigated in a compact boundary-layer wind tunnel. The drag coefficient of the fine-grained gravel surface reached the maximum value at 15% coverage and then tended to stabilize at gravel coverage 20% and greater. At a height of 4 cm, near-surface airflow on gravel surfaces can be divided clearly into upper and lower sublayers, defined as the inertial and roughness sublayers, respectively. The coefficient of variation of wind speed over gravel surfaces in the roughness sublayer was 8.6 times that in the inertial sublayer, indicating a greater effect of gravel coverage on wind-speed fluctuations in the lower layer. At a height of 4 cm, wind-speed fluctuations under the observed wind speeds were independent of changes in gravel coverage. In addition, an energy-exchange region, where sand particles can absorb more energy from the surrounding airflow, was found between the roughness and inertial sublayers, enhancing the erosional state of wind-blown sand. This finding can be applied to evaluate the aerodynamic stability of the gravel surface in the Gobi Desert and provide a theoretical basis for elucidation of the vertical distributions of wind-blown sand flux.